BRAF V600E Status and Stimulated Thyroglobulin at Ablation Time Increase Prognostic Value of American Thyroid Association Classification Systems for Persistent Disease in Differentiated Thyroid Carcinoma - Andrea Repaci; Valentina Vicennati; Alexandro Paccapelo; Ottavio Cavicchi; Nicola Salituro; Fabio Monari; Dario de Biase; Giovanni Tallini; Annalisa Altimari; Elisa Gruppioni; Michelangelo Fiorentino; Uberto Pagotto (International Journal of Endocrinology)
Background. Stimulated thyroglobulin levels measured at the time of remnant ablation (A-hTg) and BRAFV600E mutation had shown prognostic value in predicting persistent disease in differentiated thyroid cancer (DTC). The aim of this study was to evaluate the prognostic role of A-hTg combined with the BRAFV600E status in association with the revised American Thyroid Association (ATA) risk stratification. Material and Methods. 620 patients treated for a DTC were included in this study with a median follow-up duration of 6.1 years. All patients underwent total thyroidectomy followed by radioiodine ablation. Patients with positive anti-thyroglobulin antibodies were excluded. The predictive value of A-hTg was calculated by receiver operating characteristic curve (ROC curve) analysis. The Cox proportional hazard regression model, including the BRAF status, A-hTg, and ATA classification system, was assessed to evaluate the existing persistent disease risk. Results. Taken together, the BRAF status and A-hTg levels improve the ATA risk classification in all categories. In particular, in the low-risk ATA classification, only the combination of BRAFV600E+A-hTg>8.9ng/ml was associated with persistent disease (P=0.001, HR 60.2, CI 95% 5.28-687). In the intermediate-risk ATA classification, BRAFWT+A-hTg>8.9ng/ml was associated with persistent disease (P=0.029, HR 2.71, CI 95% 1.106-6.670) and BRAFV600E+A-hTg>8.9ng/ml was also associated with persistent disease (P<0.001, HR 5.001, CI 95% 2.318-10.790). In the high-risk ATA classification, both BRAFV600E+A-hTg<8.9ng/ml and BRAFV600E+A-hTg>8.9 ng/ml were associated with persistent disease (P=0.042, HR 5.963, CI 95% 1.069-33.255 and P=0.002, HR 11.564, CI 95% 2.543-52.576, respectively). Conclusions. The BRAF status and stimulated thyroglobulin levels at ablation time improve the ATA risk stratification of differentiated thyroid cancer; therefore, even A-hTg could be included in risk classification factors.